A Phoenician / Hellenistic Sanctuary at Horbat Turit (Kh. et-Tantur) - Atrash, Walid; Mazor, Gabriel; Aboud, Hanaa (Journal of Hellenistic Pottery and Material Culture, 2018)
About 4 km east of Acre, situated over a high commanding hill overlooking the Bay of Haifa in the west and Rosh Haniqra in the north, substantive ruins of a monumental podium were discovered (figs. 1–2) and excavated in August 2011. The site called Turon de Saladin, mentioned in relation to the siege of Acre (1189‒1191), was identified in the Atlas of Israel (1956 Map 5 / 1) with Tel Keisan. According to Frankel its identification should be reconsidered. As Hadia ‒ Kh. El-’Aidadiya (map ref. 164 257) should be identified with Tel Keisan, Turon de Saladin must be the hill north of the Acre-Zefat road on which Kh. et-Tantur (Tell el-Tantur; Djebel Tantur) is situated.